Simultaneous determination of dexamethasone and lenalidomide in rat plasma by solid phase extraction and ultra-performance liquid chromatography-tandem mass spectrometry: application to pharmacokinetic studies. Issue 119 (18th November 2015) - Maher, Hadir M.; Alzoman, Nourah Z.; Alshehri, Mona M.; Aljohar, Haya I.; Shehata, Shereen; Alossaimi, Manal; Abanmy, Norah O.
Abstract : Determination of dexamethasone and lenalidomide in plasma by SPE and UPLC-MS/MS for the purpose of TDM: application to pharmacokinetic studies. Abstract : An ultra-performance liquid chromatography method with tandem mass spectrometric detection (UPLC-MS/MS) has been developed and validated for the simultaneous determination of lenalidomide (LND) and dexamethasone (DEX) in rat plasma using domperidone (DOM) as an internal standard (IS). Sample preparation was performed using solid phase extraction methodology (SPE) followed by chromatographic analysis on a C 18 column (100 × 1.0 mm, i.d., 1.7 μm particle size) and a mobile phase composed of (0.1% formic acid in water) and (0.1% formic acid in acetonitrile) in the ratio of (20 : 80, v/v) at the flow rate of 0.2 mL min −1 . Electrospray ionization (EI) in the positive ionization mode using multiple reaction monitoring (MRM) was applied to detect the transitions of DEX at m / z 393 > 147, LND at m / z 260 > 149 (LND), and DOM at m / z 426 > 175. The method was validated over the concentration range of 0.01–5 ng mL −1 with a very low limit of quantitation of 0.01 ng mL −1 for both LND and DEX. Recoveries of both analytes from plasma samples ranged from 86–106% throughout their linear ranges. Intra-day and inter-day precision was evaluated and in all cases, the RSD values were within the acceptance values (<15%). The applicability of the method was extended to the determination of the pharmacokinetics of both LND and DEX, following their oral administration to rats, either alone or in combination, suggesting the applicability of the method in further clinical studies.